PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 019 SEKELADI TANAH PUTIH - Riswati Riswati; Mahmud Alpusari; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study is based on the low learning outcomes of science students of class V in Elementary School 019 Sekeladi Tanah Putih Academic Year 2016/2017. Preliminary data received by the researchers, from 28 students who achieved the value of KKM only 7 students (29.6%) with an average of 64.37. This research is a classroom action research conducted collaboratively and participatively in collaboration with science teacher class V in SD Negeri 019 Sekeladi Tanah Putih. The instrument of this study consists of learning devices used in this study based on Education Unit Level Curriculum (KTSP). Learning tools consist of syllabus, lesson plans, student worksheets and observation sheets. The result of research got the activity of teacher at first cycle of meeting I that is 60% with enough category, second meeting of cycle I that is 75% with good category. At the second meeting of meeting II is 85% with very good category and second meeting second cycle is 95% with very good category. Then the percentage of first cycle activity of the first student is 55% with enough category, the second meeting of cycle I is 75% with good category. In the second cycle of meeting I is 85% with very good category, and meeting II is 90% with very good category. The students' learning outcomes are complete before the action is held only 7 students (29.167%) with an average score of 64.37. In the daily test I cycle I the number of completed students increased to 13 students or (54.167%) with an average score of 70. Furthermore, in II repetition cycle II increased again with a total number of students who completed 21 students or (87.5%) with an average score of 84.79. The increase in student learning outcomes between the baseline score of one cycle with an average of 8.73% and between the basic score of the second cycle with an average of 31.71%. This means that the classical value obtained by students has been above the established KKM.Keywords: Problem Based Learning Model (PBL), Learning Outcomes IPA